Optimization of Polyphenol Extraction from Purple Corn Pericarp Using Glycerol/Lactic Acid-Based Deep Eutectic Solvent in Combination with Ultrasound-Assisted Extraction - Ravinder Kumar; Sherry Flint-Garcia; Miriam Nancy Salazar Vidal; Lakshmikantha Channaiah; Bongkosh Vardhanabhuti; Stephan Sommer; Caixia Wan; Pavel Somavat (Antioxidants)
Purple corn pericarp, a processing waste stream, is an extremely rich source of phytochemicals. Optimal polyphenol extraction parameters were identified using response surface methodology (RSM) by combining a deep eutectic solvent (DES) and ultrasound-assisted extraction (UAE) method. After DES characterization, Plackett–Burman design was used to screen five explanatory variables, namely, time, Temp (temperature), water, Amp (amplitude), and S/L (solid-to-liquid ratio). The total anthocyanin concentration (TAC), total polyphenol concentration (TPC), and condensed tannin (CT) concentration were the response variables. After identifying significant factors, the Box–Behnken design was utilized to identify the optimal extraction parameters. The experimental yields under the optimized conditions of time (10 min), temperature (60 °C), water concentration (42.73%), and amplitude (40%) were 36.31 ± 1.54 g of cyanidin-3-glucoside (C3G), 103.16 ± 6.17 g of gallic acid (GA), and 237.54 ± 9.98 g of epicatechin (EE) per kg of pericarp, with a desirability index of 0.858. The relative standard error among the predicted and experimental yields was <10%, validating the robustness of the model. HPLC analysis identified seven phytochemicals, and significant antioxidant activities were observed through four distinct assays. Metabolomic profiling identified 57 unique phytochemicals. The UAE technique combined with DES can efficiently extract polyphenols from purple corn pericarp in a short time.